Phosphate interactions with proteins - Fairbrother, W (1989)
﻿ Proton nuclear magnetic resonance (NMR) spectroscopy has been used to investigate the interaction of yeast phosphoglycerate kinase (PGK) with its phosphate containing substrates, ATP and 3-phosphoglycerate (3-PG). The application of one-dimensional and, for the first time, two-dimensional proton NMR techniques to this large protein has enabled specific resonance assignments to be made. Assignment has been aided by the investigation of specifically deuterated protein and site-specific mutant forms of the protein, including the isolated N- and C-domains. The effects of ATP and 3-PG binding on the proton NMR spectrum of yeast PGK have been characterised and the assigned resonances used as local probes of structural and dynamic changes. Two binding sites have been determined for the nucleotide substrate, ATP, the occupancies of which are dependent on Mg2+ concentration. One site corresponds to the catalytic site determined crystallographically. A single binding site was found for 3-PG. This binding was shown to cause highly specific conformational changes throughout the N-domain and the interdomain region, which involve the relative movement of at least three α-helices. Investigation of 3-PG binding to several site-specific mutant forms of yeast PGK revealed a critical role for arginine 168 in the propagation of these changes. The general binding of anions to yeast PGK was investigated using the paramagnetic probes [Cr(CN)6]3- and [Fe(CN)6]3-, and the diamagnetic anion [Co(CN)6]3-. The primary anion binding site was determined from [Cr(CN)6]3- broadening data and found to share some side-chains involved in 3-PG binding, namely histidine 62 and arginine 168. Evidence for a secondary anion site was found. The anion binding data is discussed in view of the complex activation/inhibition effects of anions on the catalytic activity. Investigation of the isolated N- and C-domains showed that both can fold independently and confirmed that the C-domain is a nucleotide binding domain. It appears that the presence of the interdomain residues and/or the C-terminal peptide are necessary for 3-PG binding to the N-domain. This work shows that the specificity of the substrates is in binding, as expected, but also in the motions induced in the protein as a whole.